2016
DOI: 10.1080/23774657.2016.1218804
|View full text |Cite
|
Sign up to set email alerts
|

Youth Drug Offenders: An Examination of Criminogenic Risk and Juvenile Recidivism

Abstract: Understanding the criminogenic risk factors and treatment needs of juvenile drug offenders is important because of the myriad negative outcomes that befall juveniles that are involved in drugs. A widely used juvenile risk assessment tool, the Youth Level of Service/Case Management Inventory (YLS/CMI) was utilized to explore criminogenic risk factors and treatment needs to predict recidivism. Demographic differences between drug and nondrug offenders were also examined. Results suggested that of the eight YLS/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…For instance, it could be objected that the predictive accuracy of the Central Eight might in general be lower for drug offenders and drug offences were more prevalent among offenders from Arab counties. However, to our knowledge, present evidence does not suggest a lower predictive validity of the Central Eight for drug offenders compared to other offence types (e.g., Kelly & Welsh, 2008;Papp et al, 2016). In addition, Dahle and Schmidt (2014), investigating a sample of young offenders all incarcerated for serious violence offences, reported lower predictive validities for Muslim offenders compared to offenders without an MB.…”
Section: Limitationscontrasting
confidence: 78%
“…For instance, it could be objected that the predictive accuracy of the Central Eight might in general be lower for drug offenders and drug offences were more prevalent among offenders from Arab counties. However, to our knowledge, present evidence does not suggest a lower predictive validity of the Central Eight for drug offenders compared to other offence types (e.g., Kelly & Welsh, 2008;Papp et al, 2016). In addition, Dahle and Schmidt (2014), investigating a sample of young offenders all incarcerated for serious violence offences, reported lower predictive validities for Muslim offenders compared to offenders without an MB.…”
Section: Limitationscontrasting
confidence: 78%
“…Court officers in this county were required to complete approximately 30 hours of training on the YLS/CMI before conducting their first assessment. Past research findings have shown that this training leads to reliable use of the YLS/CMI (i.e., interrater reliability and internal consistency) in the court in this study (Onifade et al, 2009;Papp et al, 2016). All youth that received a YLS/CMI between July 1, 2004 and August 31, 2010 were included in this study.…”
Section: Participantsmentioning
confidence: 89%
“…Violations of probation were not counted as recidivism. Operationalizing recidivism by the filing of a new court petition was ideal because it was the most reliably recorded incident by the court in question and has been used extensively in past research (Anderson et al, 2016; Onifade et al, 2008; Papp et al, 2016). It is important to note that a court petition does not necessarily mean that a crime occurred, which causes error in this measure of recidivism.…”
Section: Methodsmentioning
confidence: 99%